2020
DOI: 10.29252/jhc.22.1.75
|View full text |Cite
|
Sign up to set email alerts
|

The Survey of Professional Ethics Observance from Nurses' Perspective and Its Related Factors in Hamadan Medical Education Centers

Abstract: Background & aim: The issue of ethics is considered as an essential element in all health professions, especially in the nursing profession. Due to the importance of ethics in nursing practice, the present study was conducted to determine the level of professional ethics from nurses' perspective and its related factors in educational and medical centers in Hamadan. Methods: This research was a descriptive-analytical study on 287 nurses working in educational and medical centers of Hamadan in 1398, which was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In addition, in a study by Dabirian et al, 37 the level of observance of nurses ‘professional ethics from the patients’ point of view was assessed as insignificant, which may be due to differences in study participants. In the present study, the nurse, education, and research dimension has the lowest score, which is consistent with the study of Kalvandi et aland Dehghani et al 34,36 Since education is one of the basic roles of nurses and this finding shows the failure the educational role of nurses, the better role of nurses in teaching should be noted because it is effective not only on patient satisfaction but also on the patient’s ability to control the disease and treatment follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in a study by Dabirian et al, 37 the level of observance of nurses ‘professional ethics from the patients’ point of view was assessed as insignificant, which may be due to differences in study participants. In the present study, the nurse, education, and research dimension has the lowest score, which is consistent with the study of Kalvandi et aland Dehghani et al 34,36 Since education is one of the basic roles of nurses and this finding shows the failure the educational role of nurses, the better role of nurses in teaching should be noted because it is effective not only on patient satisfaction but also on the patient’s ability to control the disease and treatment follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…31 According to the results, this expectation has not been met satisfactorily. Mohajjel Aghdam et al, 32 Maarefi et al, 33 and Kalvandi et al, 34 reported the performance of nurses in observance of ethical codes at a moderate level. The results of these studies are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For many professions, various principles, rules, and ethical standards have been developed at the organizational, national, and even global levels under the title of professional ethics, which the owners of that profession are required to comply with. Professional ethics is considered a basic element in all health professions, including nursing, and it plays an important role in the moral behavior of nurses with patients and strongly affects the improvement of patients’ health [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 This results in a relatively uneven adherence to professional ethics by nursing staff, which over time can put at risk not only the quality of care but also the physical and mental health of nurses and other healthcare professionals. 11,12 Background Exploring the reasons that can help nurses comply with professional ethics is undoubtedly important. Previous studies research has mentioned ethical resilience, 13,14 the ability of individuals to maintain or restore their integrity in response to moral complexity, confusion, distress, or frustration, and communication within the organization, 15 and support from nurse leaders, 16 as important factors in helping nurses maintain ethical principles in the face of moral adversity.…”
Section: Introductionmentioning
confidence: 99%
“…10 This results in a relatively uneven adherence to professional ethics by nursing staff, which over time can put at risk not only the quality of care but also the physical and mental health of nurses and other healthcare professionals. 11,12…”
Section: Introductionmentioning
confidence: 99%